Design of spontaneously blinking fluorophores for live-cell super-resolution imaging based on quantum-chemical calculations. Issue 86 (6th October 2020) - Tachibana, Ryo; Kamiya, Mako; Morozumi, Akihiko; Miyazaki, Yoshiyuki; Fujioka, Hiroyoshi; Nanjo, Aika; Kojima, Ryosuke; Komatsu, Toru; Ueno, Tasuku; Hanaoka, Kenjiro; Yoshihara, Toshitada; Tobita, Seiji; et al.
Abstract : Spontaneously blinking fluorophores are powerful tools for live-cell super-resolution imaging under physiological conditions. Abstract : Spontaneously blinking fluorophores are powerful tools for live-cell super-resolution imaging under physiological conditions. Here we show that quantum-chemical calculations can predict key parameters for fluorophore design. We applied this methodology to develop a spontaneously blinking fluorophore with yellow fluorescence for super-resolution imaging of microtubules in living cells.